Targeting of the Plzf Gene in the Rat by Transcription Activator-Like Effector Nuclease Results in Caudal Regression Syndrome in Spontaneously Hypertensive Rats - Liška, František; Peterková, Renata; Peterka, Miroslav; Landa, Vladimír; Zídek, Václav; Mlejnek, Petr; Šilhavý, Jan; Šimáková, Miroslava; Křen, Vladimír; Starker, Colby G; Voytas, Daniel F; Izsvák, Zsuzsanna; et al. (PLoS One, 2016)
Recently, it has been found that spontaneous mutation Lx (polydactyly-luxate syndrome) in the rat is determined by deletion of a conserved intronic sequence of the Plzf (Promyelocytic leukemia zinc finger protein) gene. In addition, Plzf is a prominent candidate gene for quantitative trait loci (QTLs) associated with cardiac hypertrophy and fibrosis in the spontaneously hypertensive rat (SHR). In the current study, we tested the effects of Plzf gene targeting in the SHR using TALENs (transcription activator-like effector nucleases). SHR ova were microinjected with constructs pTAL438/439 coding for a sequence-specific endonuclease that binds to target sequence in the first coding exon of the Plzf gene. Out of 43 animals born after microinjection, we detected a single male founder. Sequence analysis revealed a deletion of G that resulted in frame shift mutation starting in codon 31 and causing a premature stop codon at position of amino acid 58. The Plzftm1Ipcv allele is semi-lethal since approximately 95% of newborn homozygous animals died perinatally. All homozygous animals exhibited manifestations of a caudal regression syndrome including tail anomalies and serious size reduction and deformities of long bones, and oligo- or polydactyly on the hindlimbs. The heterozygous animals only exhibited the tail anomalies. Impaired development of the urinary tract was also revealed: one homozygous and one heterozygous rat exhibited a vesico-ureteric reflux with enormous dilatation of ureters and renal pelvis. In the homozygote, this was combined with a hypoplastic kidney. These results provide evidence for the important role of Plzf gene during development of the caudal part of a body-column vertebrae, hindlimbs and urinary system in the rat.
Keywords: DNA vazebné proteiny; Animals; polydaktylie; heterozygot; Base Sequence; Genotype; Tail; homozygot; sekvence aminokyselin; vazba proteinů; Transcription Activator-Like Effector Nucleases; Polydactyly; Heterozygote; posunová mutace; genotyp; mnohočetné abnormality; Amino Acid Sequence; Protein Binding; Frameshift Mutation; Homozygote; TALENs; Gene Targeting; Male; Exons; ocas; sekvence nukleotidů; alely; DNA-Binding Proteins; krysa rodu Rattus; Abnormalities, Multiple; potkani inbrední SHR; Alleles; exony; Quantitative Trait Loci; zvířata; mužské pohlaví; lokus kvantitativního znaku; genový targeting; Rats; Rats, Inbred SHR